Mutations in unfolded protein response regulator ATF6 cause hearing and vision loss syndrome - Lee, Eun-Jin; Kim, Kyle; Diaz-Aguilar, Monica Sophia; Min, Hyejung; Chavez, Eduardo; Steinbergs, Korina J.; Safarta, Lance A.; Zhang, Guirong; Ryan, Allen F.; Lin, Jonathan H. (The Journal of clinical investigation, 2025)
Activating transcription factor 6 (ATF6) is a key regulator of the unfolded protein response (UPR) and is important for ER function and protein homeostasis in metazoan cells. Patients carrying loss-of-function ATF6 disease alleles develop the cone dysfunction disorder achromatopsia. The effect of loss of ATF6 function on other cell types, organs, and diseases in people remains unclear. Here, we report that progressive sensorineural hearing loss was a notable complaint in some patients carrying ATF6 disease alleles and that Atf6-/- mice also showed progressive auditory deficits affecting both sexes. In mice with hearing deficits, we found disorganized stereocilia on hair cells and focal loss of outer hair cells. Transcriptomics analysis of Atf6-/- cochleae revealed a marked induction of the UPR, especially through the protein kinase RNA-like endoplasmic reticulum kinase (PERK) arm. These findings identify ATF6 as an essential regulator of cochlear health and function. Furthermore, they support the idea that ATF6 inactivation in people causes progressive sensorineural hearing loss as part of a blindness-deafness genetic syndrome targeting hair cells and cone photoreceptors. Last, our genetic findings indicate that ER stress is an important pathomechanism underlying cochlear damage and hearing loss, with clinical implications for patient lifestyle modifications that minimize environmental and physiological sources of ER stress to the ear.